The effect of calcinated hydroxyapatite and magnesium doped hydroxyapatite as fillers on the mechanical properties of a model BisGMA/TEGDMA dental composite initially and after aging - Tamara Matic (Metallurgical & Materials Engineering, 2018)
The aim of this study was to investigate the possibility of modifying model BisGMA/TEGDMA dental composite by substituting 10 wt. % of conventional glass fillers with bioactive fillers based on calcinated nanosized hydroxyapatite (HAp) and Mg doped hydroxyapatite (Mg-HAp). HAp and Mg-HAp powders were synthesized hydrothermally. Mechanical properties: hardness by Vickers (HV) and flexural strength (Fs) were tested initially and after being stored for 28 days in simulated body fluid (SBF). The experimental composites with HAp and Mg-HAp particles showed no statistically significant difference in HV compared to the control (p>0.05) either initially or after storage. Although mean Fs values of modified composites tested initially were lower (62 MPa) than those of the control (72 MPa), after 28 days of storage in SBF Fs values were greater for modified composites (42 MPa control sample, 48 MPa HAp and Mg-HAp samples). In vitro bioactivity of BisGMA/TEGDMA composites with HAp and Mg-HAp particles after 28 days in SBF was not detected.